Successful workplace learning : moderating effect of organizational culture. - Daryoush, Younes; Silong, Abu Daud; Omar, Zoharah; Othman, Jamilah (Macrothink Institute, 2013)
A main point of this study was that successful workplace learning is depended on workplace environment and its relationship with job performance will be improved in certain organizational culture values and practices. We hypothesized that the relationship between formal, informal and incidental workplace learning with task and contextual performance would be higher in result-oriented cultures. These two hypotheses were supported. We further hypothesized and found support that workplace learning and task performance relationships are stronger in combined outcome- and innovation-oriented cultures. Our results indicate that these two cultural values complement each other in facilitating positive outcomes for workplace learning.